Perception of Neighbouring Ethnic Groups in Polyethnic Regions - Shlyakhova, Svetlana; Belova, Larisa; Bolshakova, Natalya; Shestakova, Olga; Yashmanova, Lyudmila (International Review of Management and Marketing, 2016)
The article investigates relationship between neighboring ethnic groups (Russians and Komi-Permians) traditionally living together in a common area. Relevance of the topic is due to transforming intercultural communication between large and small ethnic groups, as any social problem tends to acquire ethnic specificity today. The article presents the results of an experimental study of hetero-stereotypes of large (Russians) and small (Komi-Permians) ethnic groups. It was found that the small ethnicity perceives the large one with great care, rather negatively than positively. Respondents of the large ethnic group give four times fewer negative estimations of the small ethnic group. Awareness of the fact that a large ethnic group treats a small ethnic group better than a small ethnic group treats itself can help reduce the anxiety of small ethnic groups in dealing with large ethnic groups. Adequate knowledge about small ethnic groups will ensure scientific management of social processes involving large and small ethnic groups. Policies to improve self-esteem of small ethnic groups and a competent cultural and linguistic policy may form conditions for effective strategies of interethnic interaction in a multicultural environment. Keywords: ethnic identity; ethnic stereotypes; Komi-Permians; Russians; psycholinguistics JEL Classifications: A29, I19, I20